On Brazilian Finger-Net Caddisfly Chimarra Stephens, 1829 (Trichoptera: Philopotamidae), I: Two New Species of Chimarra (Curgia) Walker, 1860 from the Caatinga and Cerrado Biomes, Northeastern Brazil - Moreno, Lucas; Desidério, Gleison R. [UNESP]; Souza, Wagner R. M.; Santana, Vitória; Bispo, Pitágoras C. [UNESP]; Lima, Lucas R. C. (MDPI, 2025)
Despite being the subgenus with the highest number of species within Chimarra Stephens, 1829 in Brazil, information about Chimarra (Curgia) Walker, 1980 is scarce in the Brazilian semi-arid region. Beyond the discussion about the quantity of species reported for this region, there is also a temporal gap concerning original descriptions of this subgenus in Brazil. Thus, 15 years after the last description of C. (Curgia) in Brazil, we diagnosed, described, and illustrated two new species based on adult males collected in the Caatinga and Cerrado biomes in the state of Piauí, viz., Chimarra (Curgia) opala sp. nov. and Chimarra (Curgia) prata sp. nov. They can be recognized mainly by the morphology of tergum X, preanal appendage, and phallotheca spines. Moreover, they do not conform to the characteristics of any species group traditionally known in the genus. While sharing similarities with the species compared in this study, these comparisons are limited to isolated characters and do not encompass all the features representing the groups of their respective species.